2012
DOI: 10.4103/1319-3767.93818
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in prevalence of overweight and obesity in Saudi children and adolescents

Abstract: Background/Aims:There are limited data on regional variation of overweight and obesity in the Kingdom of Saudi Arabia. Therefore, the aim of this report is to explore the magnitude of these variation in order to focus preventive programs to regional needs.Setting and Design:Community-based multistage random sample of representative cohort from each region.Patients and Methods:the study sample was cross-sectional, representative of healthy children and adolescents from 2 to 17 years of age. Body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 16 publications
3
55
1
Order By: Relevance
“…However, the rates of overweight and obesity among preschool children were reported as nearly 15% and 6%, respectively [46]. A previous study done by El Mouzan et al reported overall prevalence of overweight was 21%, 13.4% and 20.1%, that of obesity was 9.3%, 6% and 9.1% in the Central, Southwestern and Northern regions from an age group of 2-17 years old [47]. A similar study done by Al-Nuaim et al revealed that the combined prevalence of overweight and obesity was 37.78% with 19.63% overweight and 18.15% obese amongst the 1270 participants [19].…”
Section: Bmimentioning
confidence: 94%
See 1 more Smart Citation
“…However, the rates of overweight and obesity among preschool children were reported as nearly 15% and 6%, respectively [46]. A previous study done by El Mouzan et al reported overall prevalence of overweight was 21%, 13.4% and 20.1%, that of obesity was 9.3%, 6% and 9.1% in the Central, Southwestern and Northern regions from an age group of 2-17 years old [47]. A similar study done by Al-Nuaim et al revealed that the combined prevalence of overweight and obesity was 37.78% with 19.63% overweight and 18.15% obese amongst the 1270 participants [19].…”
Section: Bmimentioning
confidence: 94%
“…The proportion of the total high BMI scores of the sample are alarming and therefore due consideration must be emphasized. According to national cross-sectional survey from 1994 to 1998 in five provinces of Saudi Arabia, overweight was defined as 10.68% and 12.7% for boys and girls, respectively (average 11.69%) and obesity was defined as 5.9% and 6.7% for boys and girls, respectively (average 6.3%) [46][47][48]. The latest national data revealed that the rates of overweight and obesity among school-age children have reached 23% and 9.3%, respectively.…”
Section: Bmimentioning
confidence: 99%
“…To be eligible for the study, participants answered "yes" to the following questions: Do you have one or more children between the ages of [2][3][4][5][6] …”
Section: Methodsmentioning
confidence: 99%
“…The Kingdom of Saudi Arabia (KSA) experienced change in eating habits and activities, influencing the high prevalence of overweight and obesity among Saudi children [1][2][3]. Childhood obesity causes multiple health consequences, prompting attention to childhood obesity across the globe [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…W orldwide prevalence of childhood obesity has increased at alarming rates: about one-third of the young population is within the range of overweight/obesity (1)(2)(3)(4)(5). This is especially worrying because obesity is associated with subclinical inflammation and confers an increased cardiovascular risk (6,7).…”
mentioning
confidence: 99%